Exploring the putative microRNAs cross-kingdom transfer in Solanum lycopersicum-Meloidogyne incognita interactions - Leonetti, Paola; Dallera, Debora; De Marchi, Davide; Candito, Pamela; Pasotti, Lorenzo; Macovei, Anca (Frontiers in Plant Science, 2024)
Plant-pathogen interaction is an inexhaustible source of information on how to sustainably control diseases that can negatively affect agricultural production. Meloidogyne incognita is a root-knot nematode (RKN), representing a pest for many crops, including tomato (Solanum lycopersicum). RKNs are widespread in many areas of the world and their incidence is increasing due to the current climatic changes. Since the ban on chemical nematicides, alternative solutions are sought to limit their spread, and RNA technologies can be envisioned as such tools. While endogenous microRNAs have been identified in both S. lycopersicum and M. incognita, and their roles have been related to the regulation of developmental changes (especially in roots during RKN infection), no study has looked at the miRNAs cross-kingdom potential during this interaction. Thereby, the current study proposes a bioinformatics pipeline to highlight potential miRNA-dependent cross-kingdom interactions between tomato and the phytoparasitic nematode M. incognita. The obtained results show that nematode miRNAs putatively targeting tomato genes are mostly related to detrimental effects on plant development and plant defense against pathogens. Similarly, tomato miRNAs putatively targeting M. incognita biological processes have negative effects on nematodes' digestion, mobility, and reproduction. To experimentally test this hypothesis, an in vitro feeding assay was carried out using sly-miRNAs selected from the bioinformatics approach. The results show that sly-miRNA156a soaked by juvenile larvae (J2s) affected the ability of the larvae to infect plant roots and form galls. This was also coupled with a significant downregulation of its potential target gene (Minc11367), as revealed by a qPCR analysis. Thereby, these results expand the knowledge on the